Imaging Features of Sclerosing Epithelioid Fibrosarcoma of the Pancreas: A Case Report - Xia, Weizhi; Yang, Yunjun; Huang, Yingbao (Frontiers in Oncology, 2020)
Background: Sclerosing epithelioid fibrosarcoma (SEF) is an extremely rare fibrosarcoma variant. There is no complete imaging data on SEF involving the pancreas. Herein, we report computed tomography (CT) and magnetic resonance imaging (MRI) data of a patient with SEF primarily involving the pancreas. Case presentation: A 64-year-old man was found to have a solid mass in the tail of the pancreas on unenhanced CT. He had no constitutional symptoms. Contrast-enhanced abdominal CT and MRI were performed, and the latter provided the diagnosis of a pancreatic neuroendocrine tumor (PNET). Laparoscopic distal pancreatectomy and splenectomy were performed. Anatomopathological examination and immunohistochemistry confirmed the tumor was a SEF of the pancreas. The patient had no signs of recurrence or metastasis during a 12-month follow-up. Conclusion: We report an extremely rare case of SEF in the pancreas and its characterization with CT and MRI.